A corpus-based analysis of English vocabulary input provided in K-12 textbooks used in Saudi Arabia - Alhudithi, Elham, author; Nekrasova-Beker, Tatiana, advisor; Becker, Anthony, committee member; Vogl, Mary, committee member (Colorado State University. Libraries, 2017)
The importance of a textbook becomes greater when it is the major source of foreign vocabulary input as is the case in Saudi Arabia with the English language. Given the fact that numerous studies indicated that Saudi EFL learners have a very limited vocabulary size (Albogami, 1995; Alhazemi, 1993; Alsaif, 2011), the present study is concerned with the extent to which input from textbooks contributes to building the learners' lexicon. Through utilizing range and concordance programs to analyze a corpus of 252,517 tokens, the researcher concluded that great opportunities were offered to learn the most frequent words in English, in which they had a relatively low type-token ratio, indicating a great deal of repetition and coverage. The findings obtained from the case study analysis also demonstrated that a sufficient variety of collocations, derivations, and inflections were provided to assist in deepening the learners' vocabulary knowledge. Although the learning of words goes hand-in-hand with the number of occurrences, where the more words that are repeated the greater the learning, the textbooks surprisingly denoted a shortcoming in the repetition of words. More specifically, at least 74% of newly-introduced words appeared four times or less. Another shortcoming was attributable to the distribution of newly-introduced words, where it contradicted with the literature by introducing as high as 30 new words per hour of schooling. Based on what the researcher found, several pedagogical implications were suggested for teaching vocabulary in EFL settings, varying from providing more repetition opportunities for abstract concepts that carry the central meaning in a given context to following a data-driven approach through the lexical analysis of concordance lines to promote students' noticing and long-time learning.